2004
DOI: 10.1196/annals.1297.092
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease Delay in Centenarian Offspring: Role of Heat Shock Proteins

Abstract: Cardiovascular disease is a major cause of morbidity and mortality of older Americans. We have demonstrated recently that centenarian offspring, when compared with age-matched controls, avoid and/or delay cardiovascular disease and cardiovascular risk factors. Given recent evidence suggesting that higher circulating levels of HSP70 predict the future development of cardiovascular disease in established hypertensives and a recent study demonstrating a decrease in HSP60 and HSP70 with advancing age, we hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 11 publications
3
32
0
Order By: Relevance
“…In conclusion, this study confirms the results of our pilot study of serum Hsp70 levels in centenarian offspring compared to controls (Terry et al, 2004) and those of Rea at al (Rea et al, 2001) and Jin et al (Jin et al, 2004), showing that serum Hsp70 levels are lower in those individuals that reach an advanced age. In addition, it suggests that low serum Hsp70 levels are associated with longevity independent of other covariates such as age, gender, race, income, alcohol, cardiovascular disease, and a variety of other age-related diseases.…”
Section: Discussionsupporting
confidence: 80%
“…In conclusion, this study confirms the results of our pilot study of serum Hsp70 levels in centenarian offspring compared to controls (Terry et al, 2004) and those of Rea at al (Rea et al, 2001) and Jin et al (Jin et al, 2004), showing that serum Hsp70 levels are lower in those individuals that reach an advanced age. In addition, it suggests that low serum Hsp70 levels are associated with longevity independent of other covariates such as age, gender, race, income, alcohol, cardiovascular disease, and a variety of other age-related diseases.…”
Section: Discussionsupporting
confidence: 80%
“…As a first step, we must consider the protective effect that longevity genes might confer and what effect this might have on lifespan. It has been shown that offspring of centenarians are healthier than their appropriate agematched controls, supporting the notion of inheritance from centenarians to their offspring [10,12,[16][17][18][19][20]. This observation lends support to the hypothesis that longevity genes might buffer the deleterious effect of certain genetically determined age-related diseases.…”
Section: Identification and The Interpretation Of A U-shape Pattern Osupporting
confidence: 68%
“…Extracellular Hsp70 (increased serum levels) is evident in a variety of clinical scenarios associated with physiologic stress. For example, increased extracellular Hsp70 levels are noted following strenuous exercise (180,181,(204)(205)(206)(207)(208), following cardio-pulmonary bypass in both adults (209,210) and children (Wheeler, unpublished data), in elderly adults (211,212), and in children with acute lung injury (Wheeler, unpublished data). In addition, increased extracellular Hsp70 concentrations correlate with worse outcome in a variety of inflammatory disease processes, including liver disease (213), coronary artery disease (214)(215)(216)(217), traumatic brain injury secondary to child abuse (218), pre-eclampsia (219), sickle cell disease vasoocclusive crisis (220), septic shock (221), and traumatic brain injury (222).…”
Section: Stress Proteins and Innate Immunitymentioning
confidence: 99%